A Study of Non-Functional Requirements in Apps for Mobile Devices - Corbalán, Leonardo César (2019)
Nowadays, no one questions the crucial role of Requirements Engi-neering in software systems development. Specifically, if apps are generated for execution on mobile devices, certain non-functional requirements become high-ly relevant. In this article, an experimental study on three non-functional re-quirements that are essential for the development of native and multi-platform mobile apps is detailed. These requirements are performance, energy consump-tion and storage space utilization.